A study on image enhancement methods for printed Bangla document images - Islam, Anika Binte; Chowdhury, Fahim Salam; Nusrat, Fariha; Kabir, Kazi Lutful; Sarwar, Hasan (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Xplore [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/ICIEV.2016.7760096 The Journal's website is at: http://ieeexplore.ieee.org/document/7760096/